DAMPAK DARI EVENT SAIL BANDA 2010 TERHADAP PERKEMBANGAN WILAYAH KECAMATAN BANDA - Ambon, Muhammad Ilham Ryansyah; Roychansyah, M Sani; Herwangi, Yori (Magister Pembangunan Wilayah dan Kota,Undip, 2019)
One of the main regional income sectors of Maluku Province comes from the tourism sector. As one of the main sectors to generate regional income, the tourism sector must be further developed so that the results can also be felt more optimally for the government and the community. One of the efforts carried out by the Central Government and the Regional Government of Maluku Province to develop the tourism sector is through organizing an international level tourism event, namely Sail Banda Event held in Banda District, Central Maluku Regency, Maluku Province. This study aims to evaluate the extent to which the development of the Banda Subdistrict area after the implementation of the Sail Banda Event and the impacts that have been made on the development of the Banda Subdistrict area. This is because even though the Sail Banda Event has been carried out but it is suspected that there was no impact from the holding of the event to increase the income and health of the local community in Banda District. In this study, the approach used is a qualitative deductive approach using analysis of regional development achievements.Â The results of this analyzes will be used to see the impact of organizing the Sail Banda Event. The findings of this study are that the implementation of the Sail Banda Event in Banda District does not have a significant impact on increasing the income and welfare of the community. Of the four objectives of organizing the Banda Sail Event, only one goal was achieved, namely increasing tourist visits.